Improve Quality Reporting of Observational Studies in Nursing Research: STROBS Statement - Ahmed Lateef Alkhaqani (KHD-Production, 2023)
The Strengthening the Reporting of Observational Studies (STROBS) Statement is a guidance document that an international group of methodologists has developed, researchers, editors, statisticians, and experts in order to enhance the quality of reporting for observational studies in nursing research and take into account empirical evidence and theoretical considerations. Implementing and using the STROBS statement will help protect nurses from scientific misconceptions leading to poor decision-making and practice. This article will discuss the importance of following the STROBS statement in nursing research, its key components, and how it can improve the quality of reporting observational studies. Review of literature based on previous studies and reviews derived from Scopus, PubMed, and Medline databases concerning STROBE statement guidelines. The data collection was conducted from December 2021 to April 2022. These studies were collected and filtered according to the specific criteria and used keywords such as STROBE, nursing studies, evidence-based nursing practice, cohort studies, case-control studies, cross-sectional and observational studies, and articles from the National Library of Medicine. Few papers have been published that demonstrate an appreciation of STROBE, but their descriptive features do not seem appropriate for nursing publications. In comparison to STROBE, relatively few papers mentioned primary sources or other information regarding the selection process for study participants and the observation time frame. Despite the widespread availability of reporting guidelines in medical and nursing, many researchers do not follow them.